The association between postpartum depression and air pollution during pregnancy and postpartum period: a national population study in Taiwan. (26th July 2021) - Shih, Ping; Wu, Chih-Da; Chiang, Tung-liang; Chen, Pau-Chung; Su, Ta-Chen; Cheng, Tsun-Jen; Chen, Yi-Hua; Guo, Yue Leon
Abstract: Epidemiological evidence shows the association between air pollutants and several mental health outcomes, including depression, sleep disturbance, dementia, childhood neurodevelopment and suicide. Pregnant women are believed to be more susceptible and vulnerable to environmental pollutants, and postpartum depression (PPD) is a prevalent debilitating mental disorder. However, data on the effects of exposure to air pollution during pregnancy and postpartum period on the risk of PPD remain limited. This study aimed to evaluate the association between exposure to ambient air pollution during pregnancy and postpartum period and the incidence of PPD. The Taiwan Birth Cohort Study recruited representative 12% of all newborn in 2005 and their mothers by two-stage stratified sampling, including 21 248 mother–infant pairs. The occurrence of PPD was assessed by a self-reported questionnaire. Exposure to air pollutants during pregnancy and postpartum period was estimated using hybrid kriging/land-use regression (LUR) and integrated LUR-machine learning model based on data from the air monitoring stations. Logistic regression was then conducted to determine adjusted odds ratios (aORs) of PPD in relation to air pollutants. A total of 21 188 women were included in the final analysis, among whom 3, 648 (17.2%) developed PPD within 6 months postpartum. The occurrence of PPD was significantly related to exposure to ambient concentrations of nitrogen dioxide (NO2 ) during first trimester after adjustment [aOR: 1.081 per interquartile range (10.67 ppb), 95% confidence interval: 1.003, 1.165], but not to particulate matter ⩽2.5 µ m in diameter or carbon monoxide. Exposure to ambient NO2 during early pregnancy was significantly related to the occurrence of PPD among the women investigated in this population-based study.